Willingness to compete and distributional preferences at early ages: an experimental study of Chinese schoolchildren - Dai, Ming; Cui, Chi; Ren, Tianming; Liu, Liu (Economics letters, 2025)
We conducted a lab-in-the-field experiment to examine the relationship between distributional preferences and willingness to compete with 197 Chinese children aged from 9 to 12 years old. Using a real-effort task to elicit competitive choice and a modified dictator game to estimate selfishness-fairness and efficiency-equality tradeoffs via a CES utility framework, we find that children with a strong fairness focus are significantly more likely to choose competitive schemes. Efficiency orientation is positively associated with the competitive choice, and this relationship is moderated by gender. Our findings provide novel evidence on the early emergence of economically relevant preferences.